2005
DOI: 10.1111/j.1745-4557.2005.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Microbial Growth and Improvement of Storage Quality in Fresh‐cut Pineapple After Methyl Jasmonate Treatment

Abstract: Maintaining the quality of a fresh-cut fruit or vegetable product is a major concern and a priority in the development and in the production of fresh-cut produce products of the industry. The industry has been searching for alternative methods to protect fresh-cut produce from decay and to prolong shelf life. The objective of this research is to enhance the quality and the shelf life of fresh-cut pineapple by exposure to methyl jasmonate (MJ). The exposure of the diced pineapple to a MJ emulsion at a concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…Fruit firmness maintained up to 40% ( P < 0.05) in fruit previously exposed to ethanol (1.2 mL/L) for 1 week compared with fruit subjected to traditional storage conditions throughout, whereas the effect did not persist following fruit transfer/storage for 1 week in ambient air (Table 1). MJ enrichment resulted in no change in fruit firmness during or following volatile exposure, contrasting previous reports with MJ‐treated fresh‐cut pineapple (Martinez‐Ferrer and Harper 2005). However, the exposure of papaya ( Carica papaya L. cv.…”
Section: Resultscontrasting
confidence: 99%
“…Fruit firmness maintained up to 40% ( P < 0.05) in fruit previously exposed to ethanol (1.2 mL/L) for 1 week compared with fruit subjected to traditional storage conditions throughout, whereas the effect did not persist following fruit transfer/storage for 1 week in ambient air (Table 1). MJ enrichment resulted in no change in fruit firmness during or following volatile exposure, contrasting previous reports with MJ‐treated fresh‐cut pineapple (Martinez‐Ferrer and Harper 2005). However, the exposure of papaya ( Carica papaya L. cv.…”
Section: Resultscontrasting
confidence: 99%
“…No references reporting the use of methyl jasmonate in freshcut fruits to control pathogenic microorganisms are available, although different studies have been published about the effectiveness of methyl jasmonate to reduce the spoilage of whole products of plant origin (Ayala-Zavala and others 2005). Wang and Buta (2003) reported that methyl jasmonate in concentrations of 11.2 and 22.4 μL/L applied as vapor (spotting the volatile compound onto filter paper strip hanging inside the container before the lids were covered) was effective for preventing mold growth in fresh-cut kiwifruit during 3 wk of storage at 10 • C. Likewise, Martínez-Ferrer and Harper (2005) reached 3 log CFU/g reductions of the native microbiota on fresh-cut pineapple after 12 d of storage at 7 • C when treating with an emulsion of methyl jasmonate in a concentration of 15 μL/L. In addition, those authors indicated that methyl jasmonate in the same concentration, but applied as a vapor (on cotton soaked with the volatile compound into container), was less effective in reducing the microbial population.…”
Section: Alternative Natural Antimicrobials From Plant Originmentioning
confidence: 99%
“…Plant defence responses are controlled by a complex network of regulators which include signal molecules and transcription factors. Plant resistance genes activate mechanism for specific recognition of pathogens and initiate defence responses [28,29]. The fungal infections induce morphological and biochemical changes in plants.…”
Section: Resultsmentioning
confidence: 99%